2016
DOI: 10.1111/mpp.12443
|View full text |Cite
|
Sign up to set email alerts
|

An Epichloë festucae homologue of MOB3, a component of the STRIPAK complex, is required for the establishment of a mutualistic symbiotic interaction with Lolium perenne

Abstract: SummaryIn both Sordaria macrospora and Neurospora crassa, components of the conserved STRIPAK (striatin‐interacting phosphatase and kinase) complex regulate cell–cell fusion, hyphal network development and fruiting body formation. Interestingly, a number of Epichloë festucae genes that are required for hyphal cell–cell fusion, such as noxA, noxR, proA, mpkA and mkkA, are also required for the establishment of a mutualistic symbiotic interaction with Lolium perenne. To determine whether MobC, a homologue of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…In contract to the results presented here, excessive hyphal branching by E. festucae mutants in plants almost always induces abnormalities in host morphology, such as stunted tillers (Takemoto et al, 2006, 2011; Tanaka et al, 2008; Eaton et al, 2010; Johnson et al, 2013b; Green et al, 2016). We assume that the acyA mutants did not stunt the host because hyphal distribution in the shoot apex was similar to the wild-type.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In contract to the results presented here, excessive hyphal branching by E. festucae mutants in plants almost always induces abnormalities in host morphology, such as stunted tillers (Takemoto et al, 2006, 2011; Tanaka et al, 2008; Eaton et al, 2010; Johnson et al, 2013b; Green et al, 2016). We assume that the acyA mutants did not stunt the host because hyphal distribution in the shoot apex was similar to the wild-type.…”
Section: Discussionsupporting
confidence: 55%
“…How Epichloë colonization processes are synchronized with host development is likely mediated through hyphal sensing of changes in host development that induce corresponding changes in fungal development. E. festucae genes in the stress-activated mitogen-activated protein kinase ( sakA ) (Eaton et al, 2010), pH-sensing ( pacC ) (Lukito et al, 2015) and striatin-interacting phosphatase and kinase complex ( mobC ) (Green et al, 2016) are required for regulation of hyphal growth in L. perenne , and their deletion induces aberrant hyphal distribution in plants and alters host growth and development. Production of reactive oxygen species (ROS) by E. festucae in culture and in planta is also vital for establishment of normal symbiotic associations between these organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of intrahyphal hyphae is widespread in fungi, occurring in response to hyphal and/or cellular damage (Bowman et al, 2006;Calonge, 1968;Takeshita et al, 2006). Such structures have been observed previously in CWI MAP kinase, membrane-associated protein and component of striatininteracting phosphatase and kinase complex mutants of E. festucae; chitin synthase mutants of A. nidulans, Fusarium graminearum and Colletotrichum graminicola; and glycosylphosphatidylinositol synthesis gene mutants of N. crassa and C. graminicola (Becker et al, 2015;Bowman et al, 2006;Green et al, 2016Green et al, , 2017Horiuchi et al, 1999;Kim et al, 2009;Oliveira-Garcia and Deising, 2016;Werner et al, 2007). In A. fumigatus, intrahyphal hyphae formation was promoted by treatment with caspofungin, which inhibits b-1,3-glucan synthase (Walker et al, 2015).…”
Section: Discussionmentioning
confidence: 56%
“…crassa and C . graminicola (Becker et al ., ; Bowman et al ., ; Green et al ., ; Horiuchi et al ., ; Kim et al ., ; Oliveira‐Garcia and Deising, ; Werner et al ., ). In A .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, many factors required for the development of fruiting bodies have been identified in S. macrospora (Kück et al, ; Teichert et al, ). Among these factors, the multiprotein complex striatin‐interacting phosphatase and kinase complex (STRIPAK) (Kück et al, ) has gained significant interest beyond fungal development because its components are conserved from yeasts to mammals (Table ) (Xiang et al, ; Pöggeler and Kück, ; Shim et al, ; Goudreault et al, ; Maerz et al, ; Bloemendal et al, ; Engh et al, ; Simonin et al, ; Wang et al, ; Bernhards and Pöggeler, ; Bloemendal et al, ; Santarpia et al, ; Dettmann et al, ; Nordzieke et al, ; Beier et al, ; Green et al, ; Kück et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%